2011
DOI: 10.1002/cphc.201100672
|View full text |Cite
|
Sign up to set email alerts
|

Are Unsaturated Isocyanides so Different from the Corresponding Nitriles?

Abstract: Simple unsaturated and cyclopropylic isocyanides are synthesized by an efficient and simple approach. These compounds with gradually increasing distance between the unsaturated moiety and the isonitrile group are studied by UV photoelectron spectroscopy and quantum chemical calculations, and also compared to the corresponding nitriles. The first photoelectron band of the unsaturated compounds is linked to removal of an electron from the HOMO, which corresponds to CC multiple-bond ionization in antibonding inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…We stated previously that ethynyl (―C ≡ CH) substituent increases the relative energy between the cyanide and isocyanide because of the triple bond position near the isocyanide or cyanide group. It has been reported based on vinyl and ethynyl substituted species that isocyanides with conjugated π systems and especially with triple bonds are more reactive than the corresponding cyanides (because of lower antibonding π CC –π NC ionization energies) . However this gives us only limited information about the absolute stabilities, as for example a stabilization was observed for the same bonding MO .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We stated previously that ethynyl (―C ≡ CH) substituent increases the relative energy between the cyanide and isocyanide because of the triple bond position near the isocyanide or cyanide group. It has been reported based on vinyl and ethynyl substituted species that isocyanides with conjugated π systems and especially with triple bonds are more reactive than the corresponding cyanides (because of lower antibonding π CC –π NC ionization energies) . However this gives us only limited information about the absolute stabilities, as for example a stabilization was observed for the same bonding MO .…”
Section: Resultsmentioning
confidence: 99%
“…Some of these bases were additionally purified before use by fractional vacuum distillation or sublimation techniques by using microscale compatible in‐house made high‐vacuum manifold apparatus and liquid nitrogen for cooling, when needed. Isocyanides have been synthesized as previously reported . Prepared isocyanides were collected into high‐vacuum compatible flasks, and these were stored after preparation in freezer at −70 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Vinyl, allenyl, and propargyl isocyanides were easily prepared on a gram scale 19. The samples were evaporated in a 20 cm‐long gas cell at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Of course, ethynyl isocyanide is also of a great interest, but there have been a lot of accurate spectroscopic studies [15–17] reported in the 20 years since its first synthesis 18. All these basic compounds show different interactions between the unsaturated substituent and the isonitrile group 19. Vinyl isocyanide was synthesized for the first time in 196720 and analyzed by microwave (MW)21, 22 and infrared (IR) spectroscopy 22.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation